Bridging the gap between research and practice: an assessment of external validity of community-based physical activity programs in Bogotá, Colombia, and Recife, Brazil - Paez, Diana C (Transl Behav Med, 2014)
For more than a decade, physical activity classes have been offered in public places at no cost to the participants in some Latin American cities, however, internal and external validity evidence of these programs is limited. The goals of this study were to assess, report, and compare the external validity of the Recreovia program (RCP) in Colombia, and the Academia da Cidade program (ACP) in Brazil. Interviews to assess external validity of the RCP and ACP were conducted in 2012. The interview guide was developed based on the RE-AIM framework. Seventeen key informants were selected to participate in the study. Interviews were recorded and transcribed verbatim. Transcripts were analyzed using a constant comparative qualitative method and experts validated common themes. RCP and ACP key informants reported that both programs reach underserved population. There is no information available about effectiveness. Both programs take place in public spaces (e.g., parks and plazas), which are selected for adoption mainly based on community demand. RCP and ACP offer free physical activity classes with educational and cultural components, have a strong organizational structure for implementation, and differ on schedule and content of classes. Funding sources were reported to play an important role on long-term maintenance. Facilitators and barriers were identified. Programs are similar in the reach and adoption elements; the main differences were found on implementation and maintenance, whereas information on effectiveness was not found. Reporting external validity of these programs is useful to bridge the gap between research and practice.